Evaluating the Appropriateness of English Textbook Used for Teaching English for Specific Purposes - Siti Nurhidayah; Abdurrachman Faridi; Zulfa Shakiyya (Universitas Negeri Semarang, 2023)
One of the steps in creating a course that delivers validity and relevance for all course design activities is analyzing the needs of the students. Need analysis helps teachers to identify students’ needs in learning English based on their daily needs and future needs. This study intends to evaluate the English textbook appropriateness for students and the school’s needs in ESP in the office administration program at SMK Setiabudhi Semarang. Hutchison and Waters (1987) proposed the theory that was employed in this research. The theory elaborates on the concept of need analysis in ESP that should contribute to the target and learning needs. Target needs are linked to what the students need to accomplish in the target situation, while learning needs refer to what the students need to do to learn effectively. This study applied a descriptive qualitative research approach to analyze the information gained via student surveys, teacher interviews, and document observations. The study's findings demonstrate that the English textbook used was deemed appropriate for meeting both the students and the school’s needs. The degree of appropriateness revealed that, on average, the textbook satisfied 77% of school needs and 87% of student needs. The result is expected to give a contribution to both teachers and students to evaluate their English materials in the textbook used in learning ESP.